Effect of Scanning Beam for Superficial Dose in Proton Therapy. (October 2015) - Moskvin, Vadim P.; Estabrook, Neil C.; Cheng, Chee-Wai; Das, Indra J.; Johnstone, Peter A. S.
Proton beam delivery technology is under development to minimize the scanning spot size for uniform dose to target, but it is also known that the superficial dose could be as high as the dose at Bragg peak for narrow and small proton beams. The objective of this study is to explore the characteristics of dose distribution at shallow depths using Monte Carlo simulation with the FLUKA code for uniform scanning (US) and discrete spot scanning (DSS) proton beams. The results show that the superficial dose for DSS is relatively high compared to US. Additionally, DSS delivers a highly heterogeneous dose to the irradiated surface for comparable doses at Bragg peak. Our simulation shows that the superficial dose can become as high as the Bragg peak when the diameter of the proton beam is reduced. This may compromise the advantage of proton beam therapy for sparing normal tissue, making skin dose a limiting factor for the clinical use of DSS. Finally, the clinical advantage of DSS may not be essential for treating uniform dose across a large target, as in craniospinal irradiation (CSI).